Combined effect of transcutaneous auricular vagus nerve stimulation and 0.1 Hz slow-paced breathing on working memory - Tian, Qian-Qian; Cheng, Chen; Liu, Peng-Hui; Yin, Zi-Xin; Zhang, Meng-Kai; Cui, Ya-Peng; Zhao, Rui; Deng, Hui; Lu, Li-Ming; Tang, Chun-Zhi; Xu, Neng-Gui; Yang, Xue-Juan; et al. (Frontiers in Neuroscience, 2023)
Background Previous research has found that transcutaneous auricular vagus nerve stimulation (taVNS) can improve working memory (WM) performance. It has also been shown that 0.1 Hz slow-paced breathing (SPB, i.e., breathing at a rate of approximately 6 breaths/min) can significantly influence physical state and cognitive function via changes in autonomic afferent activity. In the present study, we investigated the synergistic effects of taVNS and SPB on WM performance. Methods A total of 96 healthy people participated in this within-subjects experiment involving four conditions, namely taVNS, SPB, combined taVNS with SPB (taVNS + SPB), and sham. Each participant underwent each intervention for 30 min and WM was compared pre- and post-intervention using the spatial and digit n-back tasks in a random order four times. Permutation-based analysis of variance was used to assess the interaction between time and intervention. Results For the spatial 3-back task, a significant interaction between time and intervention was found for the accuracy rate of matching trials (mACC, p = 0.03). Post hoc analysis suggested that both taVNS and taVNS + SPB improved WM performance, however, no significant difference was found in the SPB or sham groups. Conclusion This study has replicated the effects of taVNS on WM performance reported in previous studies. However, the synergistic effects of combined taVNS and SPB warrant further research.